2017
DOI: 10.11648/j.ijsedu.20170501.11
|View full text |Cite
|
Sign up to set email alerts
|

Towards Adoption of Constructivist Instructional Approach in Learning Biology in Secondary School Students in Kenya: Addressing Learner Attitude

Abstract: Learning Biology helps learners to acquire requisite knowledge in understanding life processes for positive coexistence. In instances where learners appreciate the position of biology in life, they develop positive attitude and this is reflected in their performance. However, in Kenya, most students have continued to register poor performance in biology in national examinations and this has been attributed to negative attitude towards the sciences by most learners. To address this, changes in the educational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…As a result, research confirmed that a positive attitude being developed in prior schools' experience have great influences on motivation of students learning science (Kemp et al, 2019). Mwanda et al (2017) argue that developing positive attitude on students have great effect on both student outcomes and latter position of science in life process.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…As a result, research confirmed that a positive attitude being developed in prior schools' experience have great influences on motivation of students learning science (Kemp et al, 2019). Mwanda et al (2017) argue that developing positive attitude on students have great effect on both student outcomes and latter position of science in life process.…”
Section: Introductionmentioning
confidence: 64%
“…Mulyana et al (2018) stated that in science learning inquiry-based strategy is a constructivist approach helpful for students to develop positive attitude towards science learning. Correspondingly, inquiry-based strategy is process by which students actively explore their real-life situation with questioning and looking for answers to their questions (Mwanda et al, 2017) and used for enhancing their attitude towards science learning (Tan et al, 2020). Furthermore, study revealed that appropriately implementation of inquiry-based model increases students' attitude towards science learning (Aktamis et al, 2017;Mwanda et al, 2017).…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that when PBL approach is appropriately adopted, students are likely to realize lifelong learning skills critical for problem solving. In supporting this assertion, Mwanda, Odundo, and Midigo (2017) affirmed that adoption of a constructivist approach develops student's intrinsic interest in discovering skills for achieving teamwork, communication, as well as defending positions with evidence and sound argument. Given that PBL is anchored on the constructivist approach, effective adoption of problem solving skills will enable student to build up competence through; self-confidence, motivation, social inclusion, self-reliance, autonomy, empathy, open-minded and self-determination critical for informed reasoning in school and in society.…”
mentioning
confidence: 94%
“…Biology is a part of science whose characteristics of content need to be taught through a constructivist approach (Mwanda, 2017;Singh & Yaduvanshi, 2015). The constructivist learning principle is the process of building students' knowledge independently and gradually both socially and personally (Bächtold, 2013;Suhendi & Purwarno, 2018).…”
Section: Introductionmentioning
confidence: 99%